Studi Kesesuaian Lahan untuk Penentuan Kawasan Lindung di Hutan Lindung Konak Kabupaten Kepahiang Provinsi Bengkulu - Gunggung Senoaji (Fakultas Kehutanan Universitas Gadjah Mada, 2010)
Study of Land Suitability for Protected Area Selection in Konak Forest Protection, Kepahiang Regency, BengkuluThe study aims to determine land suitability of the area into a forest protection by using field physical factors i.e. rainfall intensity, soil type, slope, and altitude. The research is conducted in Konak Forest Protection, Kepahiang, Bengkulu. Basic method used in this research was survey, with sampling and measurement in the field. The results shows the average value of forest protected areas: slope is 0-8% with value of 20, the type of land is podsolic (sensitive to erosion) with value of 60, and rainfall intensity is under 13.6 mm per day, with value of 10, and altitude is 500 meters above sea level. The total value of the factors is 90, far below the standard value of the protected forest which should be more than 174. This means that utilization for other functions, such as recreation area, city garden or land cultivation, will be more appropriate and useful than if only defined as forests protection.